Transdermal microneedle patches as a promising drug delivery system for anti-obesogenic molecules - Sánchez-Trasviña, Calef; Coronel-Meneses, David; Escobar-Fernández, Aleyda Margarita; Mayolo-Deloisa, Karla (Frontiers in Bioengineering and Biotechnology, 2024)
Obesity, characterized by excessive storage of lipids, has become a global pandemic with high incidence levels, and its forecast is not encouraging. Currently, there are different strategies to treat obesity; however, these conventional methods have various limitations. Lifestyle changes may result in poor outcomes due to the complexity of obesity causes, pharmaceutic treatments produce severe side effects, and bariatric surgery is highly invasive. In the search for alternative treatments to fight obesity, transdermal drug delivery systems of anti-obesogenic molecules have gained particular attention. However, the diffusion of molecules through the skin is the main drawback due to the characteristics of different layers of the skin, principally the stratum corneum and its barrier-like behavior. In this sense, microneedles patches (MP) have emerged to overcome this limitation by piercing the skin and allowing drug delivery inside the body. Although MP have been studied for some years, it was not until about 2017 that their potential as anti-obesogenic treatment was reported. This article aims to summarize and analyze the strategies employed to produce MP and to embed the active molecules against obesity. Special attention is focused on the microneedle's material, geometry, array, and additional delivery strategies, like nanoencapsulation. MP are a promising tool to develop an easyaccess treatment, avoiding the digestive tract and with the capacity to enhance the anti-obesogenic activity by delivering one or more active molecules.